Tensile behavior of different anchor channel connections. (January 2022) - Cattaneo, Sara; Crespi, Pietro; Bonati, Antonio; Scamardo, Manuela
Abstract: This paper compares the behavior of two T-shaped bolts in a cold-formed anchor channel system under tension loads, typically used to connect precast reinforced concrete elements. A new sliding block patented bolt is compared with a standard commercially available one. The comparison of the mechanical behavior of the two bolts is supported by experimental investigations, analytical evaluations, and numerical analyses. The tensile load bearing capacity of the connection is examined with reference to two different working configurations: one with the bolt in the middle of the anchor channel, and the other one with the bolt aligned with the anchor embedded in concrete. The comparison of the obtained results shows a higher efficiency of the newest bolt nut thanks to the better spread of the applied tensile load along the lips of the cast-in channel. Furthermore, the results also show that the weakest working configuration of the connection is, as expected, the one above the anchor. Both the analytical and numerical models support the experimental studies, allowing a better understanding of both deformation and stress distributions in the materials. Highlights: Mechanical characterization of a new patented cast-in anchor channel. Experimental, analytical, and numerical evaluation of the anchor bearing capacity. Comparison of the results with a standard anchor channel. Effect of different working configurations.